Dynamic Parking Pricing: Comparison of Evaluation Methods. Issue 1 (January 2016) - Willson, Richard; Irish, Aiden
Dynamic parking pricing varies the cost of parking over location and time to achieve target occupancy rates. Such pricing seeks more efficient parking space use, reduced cruising for parking, and improved satisfaction with the parking experience. Evaluation practice in this field is developing as communities implement new programs. With four case studies, the programs and their evaluations are explained, and a comprehensive evaluation framework is developed. The framework differentiates between possible theory failure and program failure and distinguishes between direct, intermediate, goal, and program support outcomes. The review reveals that some metrics, such as congestion reduction, are not supported by theory or evaluation results. Other logical metrics, such as the efficiency of parking use as indicated by a ratio of district activity per parking space, are missing.